Trends in the biological functions and medical applications of extracellular vesicles and analogues - Yan Zhao; Xiaolu Li; Wenbo Zhang; Lanlan Yu; Yang Wang; Zhun Deng; Mingwei Liu; Shanshan Mo; Ruonan Wang; Jinming Zhao; Shuli Liu; Yun Hao; et al. (Elsevier, 2021)
Natural extracellular vesicles (EVs) play important roles in many life processes such as in the intermolecular transfer of substances and genetic information exchanges. Investigating the origins and working mechanisms of natural EVs may provide an understanding of life activities, especially regarding the occurrence and development of diseases. Additionally, due to their vesicular structure, EVs (in small molecules, nucleic acids, proteins, etc.) could act as efficient drug-delivery carriers. Herein, we describe the sources and biological functions of various EVs, summarize the roles of EVs in disease diagnosis and treatment, and review the application of EVs as drug-delivery carriers. We also assess the challenges and perspectives of EVs in biomedical applications.